Brief Report on The Population Survey Long-tailed Macaque (Macaca fascicularis [Raffles,1821]) in West Nusa Tenggara, Indonesia - Hadi, Islamul; Wiantoro, Sigit; Inayah, Nurul; Maharadatunkamsi, Maharadatunkamsi; Atikah, Tika Dewi; Zamroni, Yuliadi; Supardiono, Supardiono; Alfian, Muhammad Rijal; Sadewo, Imran; Mubarokah, Nurlaila; Kurniawan, Budhy; Tresnani, Galuh (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Survey on the population and distribution of long-tailed macaque (Macaca fascicularis [Raffles, 1821]) in the administrative areas of West Nusa Tenggara Province have been conducted during June-July 2024 to examine the distribution and population status on the macaque.Â  The on-road reconnaissance survey, interview and literature studies have applied to collect data. We recorded 6146 individuals from 307 groups of long-tailed macaques in eight regencies. Of the 6146 individuals of long-tailed macaques, 1532 individuals are recorded living in conservation area, while 4614 individuals live in outside conservation area, respectively.Â  The number of individuals and troops of the monkey showed us the minimum number that can be recorded. Further study needs to be conducted in addressed to dig more information on the existence of long-tailed macaque in West Nusa Tenggara. Furthermore, population information and distribution of long-tailed macaques could be the basic knowledge on the population management efforts in the future.